The Relationship of Quality On The Level of Satisfaction With Physiotherapy Services Towards Patients: Literature Review - Athalah Suhara, Akmalkhan; Prabuwinata, Yoel; Pratama, Rifqi; Alpiah , Dini Nur (International Journal of Social Research, 2024)
Hospitals are one of the various facilities owned by each country which are used to provide health services to the entire community, so that every hospital is obliged to provide quality health services to satisfy every patient it receives. Information from the Ministry of Health of the Republic of Indonesia 2018 In Indonesia, 60% of hospitals have not set service standards that can be accepted by the entire community and meet the requirements for effective service. Such as therapist qualifications, always updated information from each health worker, professionalism of health workers and methods of good communication between health workers and patients. The aim of this research is to analyze patient satisfaction with physiotherapy services using a literature review method based on Google Scholar data. We use literature from four magazines. This study used the literature review method. A literature review is an integrated analysis (not just a summary) of scientific papers directly related to research questions. The results and conclusions of four previous research publications stated that patients were satisfied with hospital physiotherapy services P<0.05.